The Influence of Content Marketing and E-WOM on Instagram on the Decision to Purchase Florist Products in Purwokerto with Customer Trust as a Mediator Variable - Ayu Putri Nidayanthi; Maliana Puspa Arum; Yosita Dwiani S (Politeknik Siber Cerdika Internasional, 2026)
Background: The rapid growth of Instagram has changed consumer purchasing behavior, with content marketing and electronic word of mouth (e-WOM) becoming important factors influencing purchasing decisions. In the florist industry, customer trust plays a key role in supporting online purchases. Objective: Instagram growth has reshaped consumer purchasing behavior, with content marketing, e-WOM, and customer trust influencing online purchase decisions. Methods: A quantitative research approach was employed using a survey of 100 respondents selected through purposive sampling. The respondents were active Instagram users who had purchased florist products via Instagram at least once during January–March 2026. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to evaluate both direct and indirect relationships among the variables. Results: The findings indicate that content marketing positively and significantly influences purchasing decisions (β = 0.182, p = 0.022), while e-WOM demonstrates a stronger positive effect (β = 0.271, p = 0.005). Customer trust significantly affects purchasing decisions (β = 0.341, p = 0.002) and serves as a significant mediator between content marketing and purchasing decisions (β = 0.125, p = 0.022), as well as between e-WOM and purchasing decisions (β = 0.148, p = 0.026). Among the predictors, e-WOM emerges as the most influential factor affecting consumer purchasing decisions. Conclusion: Content marketing and e-WOM significantly influence purchasing decisions through customer trust, with e-WOM emerging as the strongest predictor. Florist businesses should focus on content quality, customer reviews, and trust-building to increase purchase conversions.